Pecíolo de inajá (Maximiliana maripa [aubl.] Drud) como fonte de matéria prima para produção de papel na Amazônia - Viana, Álefe Lopes; Mady, Francisco Tarcísio Moraes; Carmo, Marcela Amazonas do; Guimarães, David Franklin da Silva (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The paper is one of the most important and versatile material ever developed by man. Various materials can be used for its manufacture, including the palm. Considering the abundance and the potential that represent palm trees in the Amazon, this research was designed to develop paper produced from the petiole inajá (Maximilian maripa), a very common palm tree in secondary forests of this region. Once collected, the petioles, the pulp was obtained by mechanical, chemical and semi-chemical pulping, using caustic soda and sulfur in different proportions. Assays in the manufacture of pulp, refining, mechanical tests were performed on paper. Are presented and discussed the results of the comparison of cooking, refining and strength tests on the leaves. The chemical treatment was better with soda + Sulfur (22%) shell. In general the inajá has great relevance as alternative secondary fiber, and can be used for purposes papermakers being used in packaging, gift boxes, envelopes, kraft paper, it presents great resistance rates due to its long fiber.